2003
DOI: 10.4269/ajtmh.2003.69.247
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Simplified Method for Using Molecular Markers to Predict Sulfadoxine-Pyrimethamine Treatment Failure in African Children With Falciparum Malaria

Abstract: Surveillance of molecular markers for key mutations in Plasmodium falciparum dihydrofolate reductase (DHFR) and dihydropteroate synthetase (DHPS) has been proposed as a means of predicting sulfadoxine/ pyrimethamine (SP) treatment outcomes in Africa. This study assessed the association between DHFR and DHPS mutations and standardized clinical outcomes in children treated with SP for uncomplicated malaria in Kampala, Uganda. Two mutations (DHFR Asn-108 and Ile-51) were too common to be useful predictors. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 26 publications
2
66
0
Order By: Relevance
“…Nonetheless, all these weaknesses point to the need for some caution in interpreting PCR-adjusted treatment outcomes. Molecular genotyping of P. falciparum msp1, msp2 and glurp has been used to differentiate recurrent parasites in both longitudinal surveys and randomized trials in Africa and Asia (Ranford-Cartwright et al 1997;Irion et al 1998;Brockman et al 1999;Basco & Ringwald 2000;Basco et al 2002;Cattamanchi et al 2003;Kyabayinze et al 2003;Happi et al 2004). However, the interpretation of genotyping data varies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, all these weaknesses point to the need for some caution in interpreting PCR-adjusted treatment outcomes. Molecular genotyping of P. falciparum msp1, msp2 and glurp has been used to differentiate recurrent parasites in both longitudinal surveys and randomized trials in Africa and Asia (Ranford-Cartwright et al 1997;Irion et al 1998;Brockman et al 1999;Basco & Ringwald 2000;Basco et al 2002;Cattamanchi et al 2003;Kyabayinze et al 2003;Happi et al 2004). However, the interpretation of genotyping data varies.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that categories (i-iii) represent recrudescent and (iv) new infections (Ranford-Cartwright et al 1997;Snounou & Beck 1998;Brockman et al 1999;Basco & Ringwald 2000;Magesa et al 2001;Basco et al 2002;Happi et al 2004). However, some investigators Kyabayinze et al 2003) consider that category (iii) represents a new infection because of the appearance of new alleles.…”
Section: Introductionmentioning
confidence: 99%
“…22 Parasite DNA was isolated from filter paper using the Chelex extraction method, 26 and genotypes were determined by using nested polymerase chain reaction amplification, digestion with restriction endonucleases, and visualization after gel electrophoresis as described. 23,27 Specimens were classified as wild-type, pure mutant, or mixed (both mutant and wild-type alleles detected in the same specimen).…”
Section: Methodsmentioning
confidence: 99%
“…21,22 Acquisition of a quintuple mutant parasite with all five mutations is associated with an increased risk of failure after treatment with SP. 21,23 Previous studies have not demonstrated an increase in the prevalence of antifolate resistance mutations among the uninfected household members of HIV-infected patients on long-term cotrimoxazole prophylaxis in Tororo. 24 However, there is concern that HIV-infected patients who take cotrimoxazole prophylaxis may select for antifolate-resistant parasites, especially in areas in which malaria is highly endemic.…”
Section: Introductionmentioning
confidence: 99%
“…Many reports use PCR to distinguish reinfection from treatment failure but do not specify the criteria used to distinguish each outcome. Often, if the initial and recurrent infections share any variant, then the recurrent infection is classified as a treatment failure (12,17). However, in an area of high malaria transmission, such as Malawi, if specific PfMSP1 variants are frequent in the parasite population, then a new infection containing one of these variants might be misclassified as a failure.…”
Section: Resultsmentioning
confidence: 99%